Kidney Disease and HIV Infection - Wyatt, Christina M. (Top Antivir Med, 2017)
The risk of acute and chronic kidney disease remains higher in HIV-infected persons than in the general population, and kidney disease in HIV-infected persons is associated with poor outcomes, including increased mortality. HIV-associated nephropathy occurs less frequently in the era of antiretroviral therapy. HIV immune complex kidney disease is being diagnosed more frequently, but the term is currently used to refer to a heterogeneous group of kidney diseases. Comorbid chronic kidney disease poses a growing burden in HIV-infected persons due to an overrepresentation of risk factors such as black race, diabetes, hypertension, and coinfection with hepatitis C virus. Drug-induced kidney toxicity also remains a concern. This article summarizes a presentation by Christina M. Wyatt, MD, at the Ryan White HIV/AIDS Program Clinical Care Conference held in New Orleans, Louisiana, in December 2015.